To accept or not to accept: Level of moral concern impacts on tolerance of Muslim minority practices - Magdalena Hirsch; Maykel Verkuyten; Kumar Yogeeswaran (British Journal of Social Psychology, 2019)
Living with diversity requires that we sometimes accept outgroup practices that we personally disapprove of (i.e., tolerance). Using an experimental design, we examined Dutch majority group members' tolerance of controversial practices with varying degrees of moral concern, performed by a culturally dissimilar (Muslims) or similar (orthodox Protestant) minority group. Furthermore, we examined whether arguments in favour or against (or a combination of both) the specific practice impacted tolerance. Results indicated that participants expressed less tolerance for provocative practices when it was associated with Muslims than orthodox Protestants, but not when such practices elicit high degrees of moral concern. This indicates that opposition towards specific practices is not just a question of dislike of Muslims, but can involve disapproval of specific practices. Argument framing did not have a consistent effect on the level of tolerance for the practices.
Keywords: 330; diversity; morality; Muslims; religion; tolerance